Peran Tata Kelola Pemerintahan Terhadap Pertumbuhan Ekonomi Di Asia - Febrian, Marisa; Satria, Doni (Universitas Negeri Padang, 2025)
This research investigates the impact of governance on economic growth in 47 Asian countries over the period 2013 to 2022. Adopting a quantitative approach, the research relies on secondary data sourced from the World Bank. Panel data regression analysis is employed. The Fixed Effect Model is determined to be the most suitable estimation method. Data analysis is conducted using EViews 13. The results indicate that: (1) Voice and accountability, along with political stability and absence of violence/terrorism, have a significant effect on economic growth. (2) Control variables, specifically foreign direct investment and labor force participation rate, also demonstrate significant influence. (3) Among these, the labor force participation rate consistently shows a strong positive impact on economic growth.